The impact of an educational intervention on fertility awareness of healthcare professionals - Petročnik, Petra (Obzornik zdravstvene nege, 2024)
Introduction: With couples' increasing postponement of pregnancy to later in life and the associated rising infertility rates, healthcare professionals need to be proactive in counselling on the risk factors affecting reproduction. To do so, they need specific counselling skills and evidence-based information. The aim of this study was to assess and compare participants' knowledge of fertility issues before and after an educational intervention on preconception health care.Methods: A cross-sectional observational study was conducted, using the same questionnaire to assess the pre- and post-intervention status. The questionnaire was developed on the basis of a literature review on infertility risk factors. The survey was conducted in a conference setting. Participation in the survey was voluntary and confidentiality was assured to all participants (midwives, nurses and healthcare students). The differences in participants' pre- and post-intervention knowledge were calculated using the Wilcoxon signed rank test.Results: The results of our study show an improvement in participants' overall knowledge on infertility risk factors. These improvements were statistically significant in the sections of 'Age and Fertility' and 'Environmental Hazards', while in the sections 'Pre-existing Medical Conditions' and 'Lifestyle Factors Affecting Fertility', participants already possessed comprehensive knowledge prior to the educational intervention. Discussion and conclusion: Healthcare professionals can improve their knowledge on preconception health through continuous education. Further studies need to test the long-term effects of different educational approaches.
Keywords: health care; life-long learning; preconception health; predkoncepcijsko zdravje; vseživljenjsko učenje; zdravstveno varstvo